Mapping of Tuberculosis Case and Climate Condition of Padang City - Elsa Yuniarti; Siti Fatimah; Indang Dewata; Heldi Heldi (Pascasarjana, Universitas Negeri Padang, 2020)
Padang as one of the cities in West Sumatra Province has a fairly high confirmed Tuberculosis case. The prevalence of pulmonary tuberculosis is influenced by ecological, geographic and climatic factors. Geographic Information Systems (GIS) that can be used as a tool that can show public health problems, especially health problems that are area-based. The aim of the study was to look at the distribution of positive smear pulmonary TB cases and the conditions of rainfall, humidity, temperature and wind speed with the use of the GIS web application in Padang City in 2018. Data are presented in the form of vulnerability maps and tables. The city of Padang has the highest humidity and suspected cases of AFB + in the Koto Tangah District.